2010
DOI: 10.1111/j.1751-1097.2010.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Photostabilizer in the Photoprotective Effects of a Formulation Containing UV‐Filters and Vitamin A

Abstract: Vitamin A palmitate has been used in cosmetics; however, studies report that this substance shows photoreactivity that can lead to loss of safety and efficacy. On the other hand, photostabilizers have been used to increase sunscreen photostability and consequently their safety and effectiveness. Thus, this study aimed to evaluate the influence of photostabilizers on the photoprotective effects of a cosmetic formulation containing UV-filters and vitamin A palmitate. The formulation containing UV-filters was sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Benevenuto et al . [ 27 ] also showed that formulations containing vitamin A palmitate with UV-filters combined with some photostabilizers had better protective effects on hairless mice skin than the ones without any photostabilizer. Considering that many cosmetic formulations contain combinations of vitamins, the results in the present study could also contribute to the development of more stable formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Benevenuto et al . [ 27 ] also showed that formulations containing vitamin A palmitate with UV-filters combined with some photostabilizers had better protective effects on hairless mice skin than the ones without any photostabilizer. Considering that many cosmetic formulations contain combinations of vitamins, the results in the present study could also contribute to the development of more stable formulations.…”
Section: Resultsmentioning
confidence: 99%
“…To manage the photostability of avobenzone, thus ensuring maximum efficiency, a variety of photostabilizers are typically combined with it, including other UV filters such octocrylene as illustrated in Fig. b , and excited state quenchers such as diethylhexyl 2,6‐naphthalate and ethylhexyl methoxycrylene . Whereas these formulation developments reduce photo‐degradation, they do not completely eliminate it.…”
Section: Overview Of Sunscreen Product Formulationmentioning
confidence: 99%
“…Among antioxidant activity assays, the chemiluminescence method is described by many authors as a sensitive assay to detect levels of free radicals as well as screen in vitro antioxidant activity (13). The in vivo photoprotective evaluation can be assessed as the ability of a substance to reduce UV-induced skin damage, such as erythema, compromised skin-barrier function and sunburn cell (apoptotic cell) formation when applied to hairless mouse skin before UVA ⁄ UVB irradiation (13,14). Clinical studies have been frequently used in dermatology and cosmetic areas; however, they are only qualitative.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen minutes after the last application of the formulations, mice were immobilized and exposed to UVA/UVB radiation from an Oriel 150 W Xenon arc solar simulator (Oriel Corporation, Stratford, CT). Irradiance at dorsal skin level (20 cm from the source) was ca 0.399 mW cm −2 UVB (measured at 290 nm) as calculated with a 70260 Oriel Radiant Power Meter equipped with a silicon probe and U‐340 filter, (13,14,18). Mice were irradiated for 9 min, which resulted in a cumulative UVB dose of ca 215.46 mJ cm −2 or 10.3 MED cm −2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation